Carcinoid Tumor in a Mature Thymic Teratoma: A Rare Type of Extra Cardiac Mass - Zanini, Gregoriana (Hindawi Publishing Corporation, 2012)
We describe the case of a young female affected by a thymus teratoma coexisting with carcinoid tumor.